Islamic Economics for Social Justice and Welfare Excerpt from Seerah of Prophet Muhammad SAW - Wiwin Oktasari (Seerat Studies, 2023)
Extraordinary progress and expansion of Islamic banking and finance in the last two decades have made people around the globe starting to acknowledge the role of Islamic economics. Despite many research and studies on Islamic economics been pursued by using different approaches and methodologies, studies on economics based on Seerah of Prophet Muhammad SAW are still in limited number. In fact, Prophet Muhammad SAW had applied economic and political policies which later created a just, stable and well-balanced society and a new prosperous civilization. Prophet Muhammad SAW laid organizing concepts and fundamentals of an Islamic economy. He established Baitul Maal (Federal Reserve) and adopted an anti-inflation currency. He declared a war against corruption and riba and pushed Ummah’s creativity and innovation in every field of industries and global trade. Using historical methodology, this paper attempts to extract the concepts of Islamic economy and business that were introduced by Prophet Muhammad SAW in the Madinah Period. With a deep scrutiny of the Prophetic Seerah, this paper will address the core economic principles based on Islamic teachings, which advocate social justice and welfare for the society. Keywords: social welfare, Islamic economics, Madinah economics, economy in Prophet Muhammad’s time